Same-sized fish groups increase aggressive interaction of sex-reversed males Nile tilapia GIFT strain - Pereira Boscolo, Camila Nomura [UNESP]; Morais, Rosana Nogueira; Goncalves-de-Freitas, Eliane [UNESP] (Elsevier B.V., 2011)
Animals with similar fighting ability can fight harder and longer than animals in asymmetric contests. Thus, the selection of fish by size similarity in husbandry might increase aggressive interactions, and lead to social instability in socially organized fish. We tested the hypothesis that grouping same-sized animals increases aggressive interactions between males of Genetic Improved Farmed Tilapia (GIFT). This could destabilize social hierarchy and increase social stress. We compared two treatments: a homogeneous group (HM) formed from five males ranging in size from 90.0 to 94.0 mm, and a heterogeneous group (HT) formed from five males ranging in size from 75.0 to 115.0 mm (n = 16 each treatment). The fish were kept in these groups for 6 days, in which agonistic interactions were video-recorded daily starting on the second day of grouping (10min/day - five observation sessions). Plasma cortisol levels were used to infer social stress level. The frequency of agonistic interactions was higher in the HM (mean +/- S.E.: HM = 302.06 +/- 20.13 x 50 min(-1); HT = 151.06 +/- 13.35 x 50 min(-1)). Changes in social rank occurred over time in this group, indicating social instability. However, cortisol levels (HM = 27.54 +/- 3.02 ngmL(-1); HT = 24.42 +/- 2.41 ng mL(-1)) were similar between treatments. After grouping, by comparing cortisol of animals at the extremes of the hierarchy, we observed that the subordinate fish had lower cortisol levels than dominant ones in the HT group (mean +/- S.E.: dominant = 27.98 +/- 5.93 ngmL(-1), subordinate = 12.13 +/- 3.03 ngmL(-1)), and no significant differences in cortisol levels between dominant and subordinate in HM treatment (mean +/- SE.: dominant = 26.72 +/- 6.53 ng mL(-1), subordinate = 20.62 +/- 4.76 ngmL(-1)). Thus, we conclude that grouping of similar sized fish increases the frequency of aggressive interactions and destabilizes social hierarchy. Although no significant differences were found in indicators of stress, we can conclude, based on behavior, that groups of similar-sized animals reduces the welfare in GIFT Nile tilapia because fish may suffer the effects of increased aggressive interactions, such as increased energy expenditure and probability of injuries. 2011 Elsevier B.V. All rights reserved.
Keywords: Cichlidae; Aggressiveness; Social stress; Social instability; Welfare